Spatial updating of allocentric landmark information in real-time and memory-guided reaching - Lu, Zijian; Fiehler, Katja (Cortex, 2020)
The 2-streams model of vision suggests that egocentric and allocentric reference frames are utilized by the dorsal and the ventral stream for real-time and memory-guided movements, respectively. Recent studies argue against such a strict functional distinction and suggest that real-time and memory-guided movements recruit the same spatial maps. In this study we focus on allocentric spatial coding and updating of targets by using landmark information in real-time and memory-guided reaching. We presented participants with a naturalistic scene which consisted of six objects on a table that served as potential reach targets. Participants were informed about the target object after scene encoding, and were prompted by a go cue to reach to its position. After target identification a brief air-puff was applied to the participant's right eye inducing an eye blink. During the blink the target object disappeared from the scene, and in half of the trials the remaining objects, that functioned as landmarks, were shifted horizontally in the same direction. We found that landmark shifts systematically influenced participants' reaching endpoints irrespective of whether the movements were controlled online based on available target information (real-time movement) or memory-guided based on remembered target information (memory-guided movement). Overall, the effect of landmark shift was stronger for memory-guided than real-time reaching. Our findings suggest that humans can encode and update reach targets in an allocentric reference frame for both real-time and memory-guided movements and show stronger allocentric coding when the movement is based on memory.